MODEL PENDIDIKAN EFEKTIF DAN APLIKATIF MENURUT ABDULLAH BIN SA’AD AL-FALIH - Maimun Maimun (State Islamic Institute of Madura, 2015)
Abstract: Education and teaching are the responsibility of every person, both in a broad sense and for the family level. Within the the family, the parents are having great responsibility for educating the children. Therefore, education must consider physical, psychological, and psychological development of the learners. Due to the instrumentation, the use of concepts, methods, strategies and other supporting facilities that are related one and another. Abdullah bin Sa'ad al-Falih offers an effective and applicable educational model which emphizes on caring and loving for children education within the family, clamming to meet the development and needs of children. Keywords: applicative effective education, child-friendly education, media, methods, Abdullah bin Sa’ad al-Falih